The symbolism and rhetoric of hair in Latin elegy - Burkowski, J (2013)
This thesis examines the hair imagery that runs through the works of Propertius, Tibullus, and Ovid. Comparative analysis of the elegists’ approaches to the motif, with particular emphasis on determining where and how each deviates from the cultural assumptions and literary tradition attached to each image, sheds light on the character and purposes of elegy as a genre, as well as on the individual aims and innovations of each poet. The Introduction provides some background on sociological approaches to the study of hair, and considers the reasons why hair imagery should have such a prominent presence in elegy. Chapter 1 focuses on the elegists’ engagement with the idea of cultus (‘cultivation’), and their manipulation of the connotations traditionally attached to elaborate hairstyles, of sophistication on the one hand, and immorality on the other, to suit an elegiac context. Chapter 2 looks at how the complexities of the power relationship between the lover and his mistress play out in references to violent hair-pulling. Chapter 3 focuses on the sometimes positively and sometimes negatively spun image of grey-haired lovers, as a reflection of the lover-poet’s own contradictory wishes for his relationship with his mistress; it also considers grey hair as a symbol of physical mortality, as contrasted with poetic immortality. Chapter 4 examines the use of images of loose hair (especially images of dishevelled mourning) to suggest connotations ranging from the erotic to the pathetic, and focuses on the effects the elegists achieve by using a single image to communicate multiple implications. The Conclusion considers the ‘afterlife’ of elegiac hair imagery: the influence that their approaches had on later authors’ handling of similar images.